EFFECTS OF TRANSPORT CURRENT AND COLUMNAR DEFECTS ON THE RF PENETRATION DEPTH OF NBSE2 - CHUNG, M; KUO, YK; XU, ZG; DELONG, LE; BRILL, JW; BUDHANI, RC (AMERICAN PHYSICAL SOC, 1994)
We report on simultaneous measurements of the dc critical current and rf penetration depth of superconducting 2H-NbSe2. We observed that the large peak in the dc critical current (the ''peak effect'') occurs at the same applied magnetic field H(T) as a maximum in the rf penetration depth, indicating that the anomaly in flux-line dynamics is associated with a change in flux-line pinning strength. The anomalies in the critical current and rf penetration depth disappear in a sample with a high density of columnar defects produced by Ag-ion bombardment; both superconducting and charge-density-wave phase transitions are substantially broadened by the defects.
Keywords: VIBRATING SUPERCONDUCTORS; FLUX; CRYSTALS; LATTICE; 2H-NBSE2; LINE; IRREVERSIBILITY; IRRADIATION; YBA2CU3O7; 2H-TASE2